Factors of Chinese Adolescents’ Moral Judgment Competence – Findings from Hubei Province - Zhang, Jing (ETHICS IN PROGRESS, 2012)
This paper uses MJT designed by German moral psychologist Lind as a measurement tool, selects 1933 teenagers from Wuhan, Xiangfan or Hubei province. The result shows that participants’ C-sore of different age is 16.90. Character of politic lies remarkable difference, and gender, profession, education, etc., doesn’t. But the specific characters of them have something to be concerned. On this basis, the author gives some advices and countermeasures for education departments.